Drill Method Implementation in Improving Activities and Learning Outcomes Students of Darurrahim Faith and Taqwa Vocational School, Jakarta - Nurbaiti; Baharuddin; Muthi, Ibnu (Proceeding International Conference on Education, 2023)
The quality and success of learning are also influenced by the competency and accuracy of the teacher in choosing and using learning methods. This study aims to determine the implementation of the Drill method in Islamic Religious Education lessons and the constraints faced at SMK Iman and Taqwa Darurrahim Jakarta. The research method used is qualitative with a descriptive approach by conducting interviews to gather information. The subjects of this study were students at the SMK level. This study's results indicate that applying the Drill method to PAI subjects can improve student learning outcomes at SMK Iman and Taqwa Darurrahim Jakarta. With the drill method, students do the same thing, repeatedly in earnest, to strengthen an association or perfect a skill so that it becomes permanent. The results showed that the average student learning outcomes had increased.